(untitled) (Orfeu, 2024)
This paper presents the results of an investigation into the Paulo Gustavo Law, implemented in 2023 in Brazil, a piece considered fundamental in the resumption of the Ministry of Culture. Based on a critical observation of the main text of the notice and its annexes applied in the states that received the largest volume of resources in the country, we sought to understand what role musician education has in consolidating music professionals and guaranteeing access to development in the area. The analysis dialogues with the perspective of cultural policies authors, such as Albino Rubim, José Carlos Durand, Nestor Garcia Canclini and Philippe Urfalino; from musical education, such as Marcus Pereira, Carlos Sandroni, Luis Ricardo Silva Queiroz, Luan Sodré de Souza; and the sociology of professions, such as Eliot Freidson; among others, the research shows a disproportionate distance between public teaching and promotion policies, problematizing the role of education in the constitution of music professionals.